The influence on fish and seafood consumption, and the attitudes and reasons for its consumption in the Croatian population - Marinac Pupavac, Sandra; Kenðel Jovanović, Gordana; Linšak, Željko; Glad, Marin; Traven, Luka; Pavičić Žeželj, Sandra (Frontiers in Sustainable Food Systems, 2022)
Fish makes an important part of the Mediterranean diet, which has been scientifically proven to help preserve human health by protecting against major chronic and inflammatory diseases. Eating fish and seafood is very important, not only for its proven health benefits but also for its positive impact on the environment. Due to many fish and seafood significant positive effects on human health, this study aimed to investigate the socio-demographic factors associated with the consumption of fish and seafood in the population of Primorsko-goranska County in Croatia. Another aim was to determine people´s attitudes, choices, and reasons for the consumption of fish and seafood. Self-reported data from 2910 participants were used. According to the European dietary recommendations for fish consumption, the participants were divided into two groups; the very low to low fish consumption group and the moderate to high fish consumption group, in order to examine the differences in socio-demographic and lifestyle variables, and their attitudes, opinions, and reasons for fish and seafood consumption. More fish and seafood were consumed by women, the elderly, the more educated, nonsmokers, and more physically active participants. Age, the highest level of education, and a diet even moderately adherent to the Mediterranean diet was found to significantly increase the likelihood of recommended fish consumption. Participants considered the best reasons to consume more fish lower prices, buy much more locally produced fishery products, and prefer to eat wild-caught fish rather than farmed fish. The study has found a slight increase in fish consumption, although still lower than the European average. It also showed significant socio-demographic associations, also the reasons and attitudes toward higher fish and seafood consumption of the Croatian population. The obtained research data are valuable for planning future public health programs in Croatia aimed at greater consumption of fish and seafood, as well as their promotion as an important part of a sustainable diet.